Efficiency Analysis of Natural Rubber Production in ASEAN: The Comparison of Panel DEA and Bootstrapping Panel DEA Analysis Based Decision on Copula Approach - Kewalin Somboon (2018)
© 2018, Springer International Publishing AG, part of Springer Nature. The purpose of this paper is to investigate the technical efficiency obtained from both panel data envelopment analysis (Panel DEA) and bootstrapping panel DEA methods under the assumption of error in the production process by using Copula models to compare the results between initial Panel DEA and bootstrapping Panel DEA methods. This paper provides the best tools to analyze technical efficiency and also represent the best natural rubber production efficient country by using the data of eight ASEAN countries (i.e., Brunei Darussalam, Cambodia, Indonesia, Malaysia, Myanmar, Philippines, Thailand, and Vietnam) over the period of 1961–2014 collected by the Food and Agriculture Organization of the United Nations. This study proposes policy suggestions according to the empirical results.